Study on Dietary Considerations of Wound Healing in Ayurveda - S. Tonni, Sanjeev; A. Wali, Amruta (Emerging Challenges in Agriculture and Food Science Vol. 3, 2022)
Wound healing has been the burning problem in a surgical practice because of a remarkable increase in the number of traumatic cases. Nutrition plays an essential role in wound healing and wound care practices, and nutritional support needs to be considered a fundamental part of wound management. A wound causes a number of changes in the body that can affect the healing process, including changes in energy, protein, carbohydrate, fat, vitamin and mineral metabolism. Various Ayurveda literatures, particularly, Sushrut samhita, which is said to be a ancient textbook of surgery in Ayurveda, has mentioned about the diet for the person suffering from the wound, and the author said that diet plays a very important role in the wound healing process. Sushrut–The father of surgery has scientifically classified it in a systemic manner, whose wealth of clinical material and the principles of management are valid even today. Shalya tantra (surgical branch in Ayurveda science) is one of the important branch of ayurveda, in which surgical and para-surgical techniques has described for management of various diseases. Vrana is the most important and widely described chapter of Shalya tantra. Vrana (wound) is one of them, which have been managed by human being from starting of civilization. Under the circumstances, the first thing which the men came across was the injury from different sources which caused him the vrana. Vrana is seen as debilitating and scaring disorder, usually seen affecting the human being at any age. Well balanced nutrition plays an essential role in the wound healing. Objective of this article is to know the importance of diet and dietetic considerations during the wound healing process.